Side-to-side differences in the lower leg muscle-bone unit in male soccer players - Anliker, E.; Sonderegger, A.; Toigo, M. (Medicine & Science in Sports & Exercise, 2013)
Purpose: To characterize side-to-side differences in the lower leg muscle-bone unit between the nondominant leg (NL) and the dominant leg (DL) using maximum voluntary forefoot ground reaction force (Fm1LH) during multiple one-legged hopping (m1LH) and tibial bone mass and geometry measured by peripheral quantitative computed tomography (pQCT).